Framework for a workplace wellness programme for HIV and AIDS affected and/or infected nurse practitioners - Basson, Helena Aletta (University of the Free State, 2011)
Purpose: The purpose of this study was to propose a framework for the development of a workplace well ness programme for nurse practitioners who are infected with and/or affected by HIV/AIDS in the healthcare private sector. Research objectives: The objective of the study was to identify and describe components, as well as propose a framework, necessary to develop a workplace well ness programme. Background: Nurse practitioners are daily confronted with illness, disease and debilitating health, psychosocial and economical conditions, especially in South Africa, where the prevalence of HIV/AIDS is very high amongst the sexually and economically active adult women between 15 - 49 years of age. Although the nurse practitioner perceive this state as being a negative notion to health, they accept it as a way of living and choose to adopt the positive concept of health, namely well ness, for themselves. The nurse practitioner thus experiences well ness if she is holistically sound and healthy, but acknowledges that her/his work environment and economical circumstances have a profound influence on their quality of life and sense of wellbeing. Furthermore emphasizing that nurse practitioners have the desire to stay healthy and well within an environment where they are daily confronted with HIV/AIDS. To support and help nurse practitioners reach an optimal level of positive health and wellbeing, research was done to explain the interrelationship between health and well ness and how health and well ness could be promoted in a workplace by instituting a workplace well ness programme. Research design: A descriptive research method in quantitative research design was used to obtain and explore information about the components found in the workplace that have a direct impact on the physical, psychosocial, spiritual and economical wellbeing of nurse practitioners confronted with HIV/AIDS which could be addressed by means of a workplace wellness programme. A structured questionnaire and the application of the Likert scale of measurement was presented to registered and enrolled nurse practitioners (n=232) after probable sampling based on randomisation, was done at the designated institution. Findings: The nurse practitioners indicated that they were afraid of being infected with HIV/AIDS and that they wanted to stay HIV negative. They regarded the then current management of HIV/AIDS in their workplace to be reconsidered. They were of opinion that HIV/AIDS pose a serious threat in the workplace and considered a workplace well ness programme as a priority whereby HIV/AIDS issues could be effectively addressed. The enhancement of positive health and wellbeing could be attained through applicable workplace interventions, awareness initiatives, HIV/AIDS information, health and wellness promotional services and programmes, as well as effective counsellor and peer educational initiatives. Conclusions: A framework utilizing a logic model to demonstrate the theory of change was presented that illustrated and explained the following: • Components inherent to the nurse practitioner and the workplace that influence the development of a workplace well ness programme; • A workplace well ness programme involves health, weiiness, health promotion and a structured wellness programme; • Components necessary for instituting an effective integrated HIV/AIDS workplace management strategy for the development of a workplace well ness programme for nurse practitioners affected and/or infected with HIV/AIDS.
Dissertation (M.Soc.Sc. (Nursing))--University of the Free State, 2011
Keywords: Framework; Wellness programme; HIV/AIDS; Nurse practitioner; Orem's theory; Logic model; Theory of change; Health; Wellness; Health promotion; Workplace; Quantitative